Digital Service Inequality in Transportation? An Evaluation of the KAI Access Application Using the E-GovQual Approach - Fierda Nurany; Muhammad Aan Aoliya; Li Jiahui (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2025)
The advancement of information technology has driven the transformation of public services, including Indonesia's transportation sector. However, e-Government implementation still faces challenges such as service disparities, infrastructure limitations, and low public trust. As the primary service provider, PT KAI developed the KAI Access application to improve efficiency, yet user complaints regarding system reliability (e.g., crashes during peak seasons like mudik) and feature inequality (discrepancies between long-distance and local train facilities) remain persistent issues. This study aims to evaluate the digital service quality of KAI Access using the e-GovQual approach, which covers six dimensions: system reliability, ease of use, user trust, content and interface, user support, and interaction functionality. Employing a descriptive qualitative methodology, data was collected through user interviews, literature review, and Miles and Huberman's interactive analysis. Findings indicate that while KAI Access meets basic digital service standards in ease of use (scoring 4.2/5 for booking flow usability) and trust (through secure payment authentication), it exhibits critical weaknesses in: (1) system reliability - frequent crashes during user surges due to static server capacity; (2) service inequality - premium features like seat selection being exclusively available for long-distance trains, reducing local train user satisfaction by 22%; and (3) interactivity - lacking integrated feedback channels. Recommended improvements include: adopting cloud auto-scaling (e.g., AWS/GCP solutions), standardizing core features (e.g., delay notifications), and developing multilingual AI chatbots. These findings serve as a foundation for enhancing PT KAI's services and provide a reference for e-Government development in Indonesia's public sector